Design of real-time detecting system for grain moisture in dryer - HU Yong; JIANG Yong-cheng (Shipin yu jixie)
Objective: To reduce grain mildew caused by high water content in storage. Methods: The function model of water content and detection frequency is determined by data measurement in multiple sites. A real-time monitoring system of grain moisture value in the dryer was designed based on STM32 microcontroller. Through the design of parallel plate sensor to detect the change value of capacitance of grain with different moisture content, through the hardware circuit to convert the capacitance value into frequency value. Through the single-chip microcomputer calculation can get the real-time moisture content of grain inside the dryer, and then through RS485 communication transmission to the display screen real-time display. Results: This on-line monitoring error of the set is within 0.5%, and the delay time of the real-time moisture value displayed by the upper computer is less than 0.1 s, which fully meets the requirements of engineering application. Conclusion: Through the field installation test, the system is efficient and will not cause a secondary injury to the grain.